Institutional Rhetoric Versus Local Reality: A Case Study of Burunge Wildlife Management Area, Tanzania. (May 2018) - Kicheleri, Rose P.; Treue, Thorsten; Nielsen, Martin R.; Kajembe, George C.; Mombo, Felister M.
Wildlife Management Areas (WMAs) are establishments that promote wildlife conservation and rural development in Tanzania. However, through focus group discussions, key informant interviews, a questionnaire survey, and literature review, we found that the participation of local people in both the establishment and management of the WMA was limited and rife with conflict. While benefits have materialized at the communal level, local people saw neither value nor benefit of the WMA to their livelihoods. Specifically, local people's access to natural resources got worse while private eco-tourism investors and the central government have gained financially. Contrary to the livelihood enhancing WMA rhetoric, top-down institutional choices have sidelined democratically elected Village Governments and successive legislative adjustments disenfranchised and dispossessed them and their constituencies. We conclude that village governments should consistently demand for their legal rights to the resources on their land until the WMA approach to conservation and development is democratized.